An autonomy perspective in theological ethics on transgenic food production - Russell, Cathriona (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2006)
Transgenic food organisms are microorganisms, plants and animals that have been transformed genetically using gene-transfer techniques. These recently- developed techniques have the potential to impact on food, agriculture and the environment in ways that are both profound and irreversible. This study begins, in Chapter 1, by investigating the discoveries, benefits and unintended outcomes from the adoption of these techniques. The issue of food safety and the strategies of policy makers and environmental managers are presented and critiqued. The contributions that the natural sciences and economics make to the descriptive aspects of the concept of sustainability are evaluated.
Keywords: Religion, Ph.D.; Ph.D. Trinity College Dublin